Sphingosine-1-phosphate promotes PDGF-dependent endothelial progenitor cell angiogenesis in human chondrosarcoma cells - Wang, Chao-Qun (Aging (Albany NY), 2019)
The malignant bone tumors that are categorized as chondrosarcomas display a high potential for metastasis in late-stage disease. Higher-grade chondrosarcomas contain higher levels of expression of platelet-derived growth factor (PDGF) and its receptor. The phosphorylation of sphingosine by sphingosine kinase enzymes SphK1 and SphK2 generates sphingosine-1-phosphate (S1P), which inhibits human chondrosarcoma cell migration, while SphK1 overexpression suppresses lung metastasis of chondrosarcoma. We sought to determine whether S1P mediates levels of PDGF-A expression and angiogenesis in chondrosarcoma. Surprisingly, our investigations found that treatment of chondrosarcoma cells with S1P and transfecting them with SphK1 cDNA increased PDGF-A expression and induced angiogenesis of endothelial progenitor cells (EPCs). Ras, Raf, MEK, ERK and AP-1 inhibitors and their small interfering RNAs (siRNAs) inhibited S1P-induced PDGF-A expression and EPC angiogenesis. Our results indicate that S1P promotes the expression of PDGF-A in chondrosarcoma via the Ras/Raf/MEK/ERK/AP-1 signaling cascade and stimulates EPC angiogenesis.